The synthesis and unexpected solution chemistry of thermochromic carborane-containing osmium half-sandwich complexes. Issue 4 (24th December 2015) - Pitto-Barry, Anaïs; South, Amy; Rodger, Alison; Barry, Nicolas P. E.
Abstract : The functionalisation of the 16-electron complex [Os(η 6 - p -cymene)(1, 2-dicarba- closo -dodecarborane-1, 2-dithiolato)] (1 ) with a series of Lewis bases to give the corresponding 18-electron complexes is reported. Abstract : The functionalisation of the 16-electron complex [Os(η 6 - p -cymene)(1, 2-dicarba- closo -dodecarborane-1, 2-dithiolato)] (1 ) with a series of Lewis bases to give the 18-electron complexes of general formula [Os(η 6 - p -cymene)(1, 2-dicarba- closo -dodecarborane-1, 2-dithiolato)(L)] (L = pyridine (2 ), 4-dimethylaminopyridine (3 ), 4-cyanopyridine (4 ), 4-methoxypyridine (5 ), pyrazine (6 ), pyridazine (7 ), 4, 4′-bipyridine (8 ) and triphenylphosphine (9 )) is reported. All 18-electron complexes are in equilibrium in solution with the 16-electron precursor, and thermochromic properties are observed in some cases (2, 3, 5, 8, and9 ). The binding constants and Gibbs free energies of the equilibria are determined using UV-visible titrations and their stabilities investigated. Synthetic routes for forcing the formation of the 18-electron species are proposed, and analytical methods to characterise the equilibria are described.